Protein requirement of juvenile fish Metinnys orinocencis (Characiformes: Characidae) - Velasco Garzon, Juan Sebastian (2020)
Protein requirement of juvenile fish Metinnys orinocencis (Characiformes: Characidae). Introduction: Dollar fish, Metynnis orinocensis, is one of the ornamental species native to Colombia with great importance in the international market. They inhabit mainly permanent lagoons and flood areas to the basins of the Amazon and Orinoco rivers. This specie has been reproduced in captivity. However, information concerning the effects of feeding on the productive performance of the specie under culture conditions is very scarce or null. Objective: To evaluate the protein requirement of juveniles M. orinocencis. Methods: We used 425 M. orinocencis fingerlings with a mean weight 0.5 ± 0.1 g and mean length 2.7 ± 0.3 cm, which were randomly distributed in seven treatments with three replications for each, in a closed recirculation system with constant aeration and fed until apparent satiety, two times a day for 60 days. Seven diets were formulated varying the protein level (20, 24, 28, 32, 36, 40 and 44 % PB). The following parameters were evaluated: weight gain, feed intake, length increase, apparent feed conversion rate, specific growth rate, protein assimilation efficiency and survival rate. The protein requirement was estimated, using the weight gain, by second-order polynomial regression analysis. Results: The growth data show a gradual increase in the weight gain in relation to the protein level in the diet, until maximum gain of 2.56 g in the fish fed with 32 % PB. The apparent food conversion showed a progressive decrease as the protein level was increased, being for 20 %, 2.9 and for 40 % 1.9. Conclusions: Considering the results of weight gain, the optimal crude protein requirement for M. orinocencis is 34.3 %.